2013
DOI: 10.1111/appy.12051
|View full text |Cite
|
Sign up to set email alerts
|

Young female survivors of sexual abuse in Malaysia and depression: What factors are associated with better outcome?

Abstract: Introduction:Research in the field of child sexual abuse is lacking in Malaysia. The aims of this study are to identify the association between sociodemographic factors and depression among sexually abused females. Methods: A cross-sectional study was conducted among 51 young sexually abused female attendees at the Suspected Child Abuse and Neglect (SCAN) clinic of Hospital Kuala Lumpur, a tertiary referral centre. Upon obtaining informed consent from participant and guardian, participants were screened for de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Emotional probems are closely related to anxiety, depression and anger caused by the stress they experience. In accordance to studies conducted by local researchers, they reported that victims of sexual abuse experienced confusions, guilt, fear, self blaming, emotional and trapped with the incidents (Wahab et al, 2013). This clearly shows that the effects of abuse are really serious as they will disrupt emotional balance and well being which later affect the individuals' psychological stability into adulthood.…”
Section: 2supporting
confidence: 74%
See 1 more Smart Citation
“…Emotional probems are closely related to anxiety, depression and anger caused by the stress they experience. In accordance to studies conducted by local researchers, they reported that victims of sexual abuse experienced confusions, guilt, fear, self blaming, emotional and trapped with the incidents (Wahab et al, 2013). This clearly shows that the effects of abuse are really serious as they will disrupt emotional balance and well being which later affect the individuals' psychological stability into adulthood.…”
Section: 2supporting
confidence: 74%
“…Although abuse cases in Malaysia are getting worse, studies on cases and victims are unpopular and difficult to find (Wahab, Tan, Marimuthu, Razali, & Muhamad, 2013) especially those related to psychosocial adjustments studies involving victims of abuse are limited may be due to difficulties to access the respondents (Wahab et al, 2013). Very little information regarding life and roles of residential care are known in Malaysia (Raj & Raval, 2013).…”
Section: Problem Statementmentioning
confidence: 99%
“…Child sexual abuse is one of the most stressful life events and is the outcome of a set of interrelated familial, social, psychological, and economic factors. CSA is associated with many adverse consequences, including physical and mental health problems, substance abuse, and criminality (Wahab et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This so-called "unconsented" component of the sexual relationship may contribute to negative emotional outcomes and conflict in the abused victim, as documented in previous studies. 27,28 The lack of attention and loving relationships at home as described by some participants had driven them to desperately find happiness in relationships outside of the home; not surprisingly they would fall for any boy who claimed to love them and wanted to be their boyfriend. 7,25,29 These findings suggest the importance of imparting teenagers with the correct understanding of romantic relationship, physical boundaries in relationships and preserving own dignity and virginity until marriage.…”
Section: Social Factorsmentioning
confidence: 99%